Effect of torsion on the undrained limiting lateral resistance of piles in clay - Georgiadis, K; Sheil, B (ICE Virtual Library, 2019)
The behaviour of piles subjected to lateral loads has been explored by a number of investigators over the past five decades. However, the vast majority of previous literature have ignored the potential influence of additional torsional effects due to horizontal eccentricities of the applied lateral loads. In this paper, an upper bound mechanism and a lower bound stress field are presented for the calculation of the ultimate combined torsional and lateral loads on single piles in clay. The corresponding analytical upper and lower bound plasticity solutions are shown to be in excellent agreement, bracketing the theoretically exact failure loads with an error of less than 0.5%. Two-dimensional finite element analyses are also presented and the computed ultimate loads and observed failure mechanisms are shown to compare very well with the plasticity solutions. Based on the numerical results and analytical solutions, failure load interaction diagrams and a simple empirical equation are presented that allow the calculation of the lateral bearing capacity factor for any level of applied torsion and pile-soil adhesion factor. It is demonstrated that the effect of torsion can be very significant, causing reduction in lateral bearing capacity of up to 50% and therefore should be considered in design.